TEORI MANU DAN KUALITAS MANUSIA SETIAP JAMAN MENURUT PUSTAKA UPANISAD DAN PURANA - Ni Kadek Berliana Diah (Perkumpulan Organisasi Profesi DPP Dosen Hindu Indonesia (DHI) Bekerja sama dengan Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar dan Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2024)
Humans as rational beings are often called atma or spirit. In the Upanisad it is called “atma” or he is Brahman. Brahman is the principle of the universe. As living beings, humans ask for guidance through God word as contained in the Purana and Upanisad Librearies. The concept of manu theory and human quality at all times in literacy is actually very much found in the Veda and their codifications. One part of codifications of the Veda which contains the manu theor and humans qualities at all times in the Purana and Upanisad. The Purana has an important position and strategy in the order of the Veda and Hindu Literature. The purpose of this study was to analyze Manu Theory and human quality at all times according to the Purana and Upanisad using a qualitative descriptive research methode. The conclusion of this study shows that the concept of manu theory and human quality at all times according to the Purana and Upanisad, it can be seen that Hindu have a sense of pride and increasingly believe in the teachings of Hinduism as a proper guide to lead their lives in navigating life in this world of propan and the natural sunya loka.Humans as rational beings are often called atma or spirit. In the Upanisad it is called “atma” or he is Brahman. Brahman is the principle of the universe. As living beings, humans ask for guidance through God word as contained in the Purana and Upanisad Librearies. The concept of manu theory and human quality at all times in literacy is actually very much found in the Veda and their codifications. One part of codifications of the Veda which contains the manu theor and humans qualities at all times in the Purana and Upanisad. The Purana has an important position and strategy in the order of the Veda and Hindu Literature. The purpose of this study was to analyze Manu Theory and human quality at all times according to the Purana and Upanisad using a qualitative descriptive research methode. The conclusion of this study shows that the concept of manu theory and human quality at all times according to the Purana and Upanisad, it can be seen that Hindu have a sense of pride and increasingly believe in the teachings of Hinduism as a proper guide to lead their lives in navigating life in this world of propan and the natural sunya loka.